The Principle of "The Judgment on Something Based Fromhis Perception" and its Applications in Contemporary Fatwas Based on Decision of The Muzakarah Mufti Malaysia Committee - Zulfaqar Mamat; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Lukman Abdul Mutalib (Usuli Faqih Research Centre PLT, 2024)
Al-Qanatir: International Journal of Islamic Studies Volume: 33 No: 3 (page: 665–677)